1999
DOI: 10.1139/f99-087
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salmon spawner densities on stream productivity in Southeast Alaska

Abstract: Abstract:We conducted this study to determine the relationship between salmon spawner abundance and stream biofilm and benthic macroinvertebrate abundance in Southeast Alaska. Experiments took place in outdoor artificial and natural streams. Six pink salmon (Oncorhynchus gorbuscha) carcass treatments (0.00, 1.45, 2.90, 4.35, 5.80, and 7.25 kg wet mass) placed in artificial channels were subsampled repeatedly for biofilm ash-free dry mass (AFDM), chlorophyll a, and macroinvertebrates. In a small (nonanadromous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 24 publications
6
107
1
Order By: Relevance
“…assimilate nutrients in marine ecosystems and deposit those nutrients in freshwater ecosystems in the form of gametes, excretions, and carcasses. In turn, the nutrients support resident fish populations (e.g., Bentley et al 2012), aquatic macroinvertebrates (e.g., Wipfli et al 1999), terrestrial vegetation (e.g., Hocking and Reynolds 2011), and terrestrial predators (e.g., Holtgrieve et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…assimilate nutrients in marine ecosystems and deposit those nutrients in freshwater ecosystems in the form of gametes, excretions, and carcasses. In turn, the nutrients support resident fish populations (e.g., Bentley et al 2012), aquatic macroinvertebrates (e.g., Wipfli et al 1999), terrestrial vegetation (e.g., Hocking and Reynolds 2011), and terrestrial predators (e.g., Holtgrieve et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…As cross-ecosystem subsidies, these MDN fluxes can be crucial resources for sustaining productivity and influencing biodiversity of the recipient ecosystems (Naiman et al 2002) by enhancing trophic pathways in oligotrophic freshwaters (Kline et al 1997). MDN can stimulate autotrophic production in streams, and dissolved organic matter (DOM) released by decomposing carcasses fuels microbial metabolism, and thereby increases productivity and enhances trophic dynamics (Bilby et al 1996;Wipfli et al 1999). Salmon carcasses are also directly consumed by macroinvertebrates (Kline et al 1997;Minakawa & Gara 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As several authors have demonstrated, subsidies (or their exclusion) can lead to trophic cascades and other community-level impacts (e.g., Nakano et al 1999;Sato et al 2016). There are certainly many examples of subsidies boosting production at lower trophic levels that contribute to bottom-up increases at higher trophic levels (e.g., Wallace et al 1999;Wipfli et al 1999). Other considerations of how subsidies might contribute to, or reduce, stability are emerging (e.g., Rosenzweig 1971;Nowlin et al 2007;Jones and Lennon 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several examples of such relations have been published. Wipfli et al (1999) experimentally demonstrated an asymptotic response of algae and freshwater invertebrates to incremental increases of salmon subsidies in experimental channels and a small natural stream in Alaska. Doseresponse relationships at broader spatial and temporal scales would advance our understanding of quantitative subsidy effects on consumers and ecosystems.…”
Section: Alternate Trajectories Of Consumer Population Responses To Smentioning
confidence: 99%
See 1 more Smart Citation